Agile Management Of Sustainable Development - Circular Economy - Sałek, Robert (Journal of Positive Management, 2023)
Purpose: The goal of the article is to create a model whose management method will take into account individual needs (client, entrepreneur), implementing the standards of global economic sustainability. The created model allows defining the Sustainable Development Goals in terms of the environmental dimension of the circular economy. Methodology/Approach: For article purpose, circular economy was used as a method improving the chances of achieving the goals of sustainable development. The statistical significance of the variables were checked for obtain data. In addition, this process was supported by the Deming cycle in order to be able to respond to changes using the agility methodology. Findings: The results of the research allowed to identify the most important (SDGs), which, when combined with the trends of the industry/sector, formed a balanced loop taking into account all participants and their needs. Implications/limitations: Managing a company according to global standards is a big challenge. The results of an analysis of own needs (an enterprise) should correlate with the needs of stakeholders in the supply chain and with the direction of development of the industry/sector in order to support the domestic economy and be competitive on global markets. Originality/value: Study explains undertaken activities for implementing process of correlation between entities which must take into account the good of the individual and, above all, of the general public. Keywords: sustainable development, agility, circular economy, organizational improvement Paper type: Research paper